CODE SWITCHING ANALYSIS IN CLASSROOM INTERACTIONS IN HUSNUL KHOTIMAH ISLAMIC SENIOR HIGH SCHOOL - Yuli Yulyana (University of Kuningan, 2012)
Abstract: This study examines types, functions, teacher’s reasons and students’ responses of code switching in classroom interactions in school context at Husnul Khotimah Islamic Senior High School. This study focuses on analyzing English teacher’s utterances at eleventh grade and their students’ utterances by using Poplack and Gumperz theory. The method of this study is descriptive qualitative. The data of the study is in the form of written recording utterances during teaching and learning process in the classroom, interview and questionnaire. Based on the analysis of the data, this study concludes that the teacher used code switching in order to give particular purpose in delivering the teachers’ feelings during teaching and learning process. The language change often makes the teacher and the students feel better and more meaningful in conveying and obtaining their feelings. Concisely, code switching not only represents teachers’ competence but also shows particular purposes. Keywords: code switching, classroom, interactions